Comparative analysis of human and mammalias genes of protein ortologs of cytochrome P450 2E1 - Duplij, D.R.; Maksymchuk, O.V.; Duplij, V.P.; Chaschin, N.A. (Вiopolymers and Cell, 2010)
Aim. To carry out a comparison analysis of nucleotide sequences for the cytochrome P450 2E1 protein ortologs genes and reestablish the connection of gene evolution with nucleotide content. Methods. In silico: BLAST, ClustalW, MEGA4, PHP. Results. A general phylogeny of CYP2E1 genes is described. The most affinity is found for human translated sequences with Pan troglodytes. The transition C > T is the most often, it occurs in introns by 2.6 times more than in exons. The correlation of keto-amino skew of CYP2E1 genes and evolution age of species is stated. Conclusions. The analysis carried out in the paper allows us to assume that a common ancestor of the CYP2E1 protein isoform lived before the divergence between rodent and Primates orders, i.e. 70 million years ago. The single nucleotide substitution is accumulated in introns during evolution. Цель. Провести сравнительный анализ нуклеотидных последовательностей генов ортологичных белков цитохрома Р450 2Е1 и установить связь эволюции гена с нуклеотидным составом. Методы. In silico: BLAST, ClustalW, MEGA4, PHP. Результаты. Изучены особенности общей филогении генов CYP2E1. Наибольшее родство транслируемой последовательности гена CYP2E1 Homo sapiеns обнаружено с Pan troglodytes. Выявлено, что транзиция С Т встречается в интронах в 2,6 раза чаще, чем в экзонах. Установлена связь между кето-аминовой асимметрией генов CYP2E1 и эволюционным возрастом вида. Выводы. На примере CYP2E1 показано, что в течение эволюции интронный состав генов изменяется в сторону увеличения количества гуанина и тимина. Таким образом, величину кето-аминовой асимметрии можно использовать как дополнительный критерий эволюционного анализа. Мета. Провести порівняльний аналіз нуклеотидних послідовностей генів ортологічних білків цитохрому Р450 2Е1 і встановити зв’язок еволюції гена з нуклеотидним складом. Методи. In silico: BLAST, ClustalW, MEGA4, PHP. Результати. Описано особливості загальної філогенії генів CYP2E1. Найбільшу спорідненість трансльованої послідовності гена CYP2E1 Homo sapiеns виявлено з Pan troglodytes. Визначено, що транзиція С Т зустрічається в інтронах у 2,6 разу частіше, ніж в экзонах. Встановлено зв’язок між кето-аміновою асиметрією генів CYP2E1 і еволюційним віком виду. Висновки. На прикладі CYP2E1 показано, що впродовж еволюції нуклеотидний склад інтронів змінюється у напрямку збільшення кількості гуаніну і тиміну. Таким чином, величину кето-аміновой асиметрії можна використовувати як додатковий критерій еволюційного аналізу.